Pelatihan Pembuatan Mesin Spinner Kripik Ubi Madu Berpenggerak Motor Listrik Pada Karang Taruna Orpega 02 (Organisasi Pemuda Erlangga) Desa Wisata Tawangmangu Jawa Tengah - yoga fakhrudi; Kholis Nur Faizin; Agus Choirul Arifin; Indah Puspitasari; Rahayu Mekar Bisono; Yuli Astuti (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2023)
In the food processing industry, such as various types of crackers, various fried peanuts and various other packaged foods, the durability and durability of these food products must of course be given great attention. One of the reasons why various foods are not durable and expire quickly is the high oil content contained in these various foods. Manually draining oil is certainly not effective for the production of various foods in large quantities on an industrial scale. For that we need a tool or machine that can drain and reduce the oil content that is still contained in these various foods. The machine used is honey sweet potato chip spinner machine. Tawangmangu Village, Tawangmangu District, Central Java is known as a tourist area which is located on the slopes of Mount Lawu with various kinds of tourist beauty presented. Tourists often come to enjoy the natural beauty of Tawangmangu which is also rich in natural products, one of which is sweet potato honey. However, local residents cannot maximize honey sweet potato as a special food which is used as souvenirs for tourists, so there is a need for an effort to engineer food processing made from honey sweet potato in the form of procurement and training of electric powered honey sweet potato chip spinner machines for Karang Taruna Orpega 02 (Organization Erlangga Youth) in the Tawangmangu Village, Central Java. At the time of implementation, Mitra's enthusiasm was very large to take part in a series of training events for making food slicer spinners. There were 20 members of the youth group who took part in a series of training activities.